2014
DOI: 10.1186/1471-2334-14-230
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the occurrence of embolic events: an analysis of 1456 episodes of infective endocarditis from the Italian Study on Endocarditis (SEI)

Abstract: BackgroundEmbolic events are a major cause of morbidity and mortality in patients with infective endocarditis. We analyzed the database of the prospective cohort study SEI in order to identify factors associated with the occurrence of embolic events and to develop a scoring system for the assessment of the risk of embolism.MethodsWe retrospectively analyzed 1456 episodes of infective endocarditis from the multicenter study SEI. Predictors of embolism were identified. Risk factors identified at multivariate ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
9
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(83 citation statements)
references
References 40 publications
7
53
9
1
Order By: Relevance
“…These changes have important implications for the modern management of IE [2]. Several international and Italian studies have shown an increase in elderly and chronically ill patients with IE [1,[3][4][5][6][7].…”
Section: Sirmentioning
confidence: 99%
“…These changes have important implications for the modern management of IE [2]. Several international and Italian studies have shown an increase in elderly and chronically ill patients with IE [1,[3][4][5][6][7].…”
Section: Sirmentioning
confidence: 99%
“…In our study, the relationship between the length of vegetation and systemic embolism was not observed, but we did prove that high mobility of vegetation is an independent risk factor of embolism, which is in line with the most recently published data 18,20,24 . Two simple calculator systems for predicting embolic risk upon admission of patients with IE have been recently designed; one French 25 and one Italian 26 . Both include S. aureus infection as an excellent predictor of embolic risk.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of embolization is associated with large vegetation size and hyphal morphology of vegetations in Haemophilus endocarditis [8]. In a study of all cause endocarditis, vegetations greater than 10 mm exhibited 2.8 greater odds of embolization [9]. More than half of patients with Haemophilus parainfluenzae endocarditis have no predisposing valvular disease, although congenital and iatrogenic abnormalities of the myocardium are common as among all cases of endocarditis [8].…”
Section: Discussionmentioning
confidence: 99%